2020
DOI: 10.1155/2020/8480193
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Serum Vascular Endothelial Growth Factor Levels and Stages of Diabetic Retinopathy and Other Biomarkers

Abstract: Aim. This study aims to measure serum vascular endothelial growth factor (VEGF) levels in a sample of Jordanian patients and to determine their relationship with the different stages of diabetic retinopathy. It also explores the correlation between VEGF concentrations and different biochemical and demographic findings. Materials and Methods. A total of 167 adults participated in the study. Participants were divided into two main categories: patients with diabetes mellitus (DM) type 2 without diabetic retinopat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 43 publications
1
12
0
Order By: Relevance
“…In addition to the SRGN level, biomarkers such as FBG level and HbA1c level showed statistically significant differences among the three groups. This finding was consistent with the previously reported HbA1c level associated with the severity of DR, and the FBG level was also associated with DR's occurrence 35. We further used ROC analysis to analyze the diagnostic value of SRGN for DR. As expected, SRGN can differentiate between DR and T2DM patients, and healthy populations with the AUC results from all are higher than 0.8.…”
supporting
confidence: 90%
“…In addition to the SRGN level, biomarkers such as FBG level and HbA1c level showed statistically significant differences among the three groups. This finding was consistent with the previously reported HbA1c level associated with the severity of DR, and the FBG level was also associated with DR's occurrence 35. We further used ROC analysis to analyze the diagnostic value of SRGN for DR. As expected, SRGN can differentiate between DR and T2DM patients, and healthy populations with the AUC results from all are higher than 0.8.…”
supporting
confidence: 90%
“…Many studies have found that VEGF is involved in the pathogenesis of diabetic complications [20], [21]. As we know that hyperglycemia-induced diacylglycerol, a lipid molecule, activates protein kinase C in the vascular tissues, and then turn promotes VEGF signaling, resulting in diabetic microvascular complications [22].…”
Section: Discussionmentioning
confidence: 99%
“…Using a 5% margin of error and a power of 90%, power analysis revealed that a minimum of 20 DR patients would be needed to detect statistical significance in comparison to non-DR controls. 17 , 18 …”
Section: Methodsmentioning
confidence: 99%
“…Data provided by participants as well as information regarding required investigations have been verified through reviewing participants’ hospital records. 17 , 18 The second section of the questionnaire evaluated patients’ practices by asking participants about the following parameters: frequency of physical exercise, regular weight checkup, DM diet status, level of compliance to diet, having a glucose checking device at home, frequency of glucose checking, periodic annual visit to the ophthalmologist, and the cause of the first clinic visit. The questionnaire’s final section evaluated patients’ awareness about DM and DR.…”
Section: Methodsmentioning
confidence: 99%